COMPARATIVE ANALYSIS OF STOCK PRICES AND TRADING VOLUME ACTIVITY DURING COVID-19 - Silvia Hendrayant; Wachidah Fauziyanti; Eni Puji Estuti (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. Since the first case of the covid-19 in Indonesia was announced on March 2nd 2020, the impact is not only on the health sector but has an impact on various aspects of life and has had a major impact on economic traffic.This research aims to find outthe significant difference between stock prices and trading Volume activity (Case Study on LQ-45 issuers listed on the IDX). These data have been taken for 31 days before and 31 days after the first announcement of covid-19 corona virus in Indonesia. In this study has been used 43 sample of LQ45 companies that provide complete data on a daily basis and have published on the Indonesia Stock Exchange (IDX). This research uses Wilcoxon Signed Ranks Test. The data processing results showed that there is a significant difference stock price between before and after the first announcement of the covid-19 case in Indonesia. This is indicated by the significance value of 0.00 < 0.05, which the stock price has decreased compared to before the covid-19 case. As for the trading volume activity also showed difference significant, which the significance value is 0.00 < 0.05. The transaction volume after the announcement of shares shows an decreasing value.